2001
DOI: 10.2527/2001.793745x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pasture sward height and concentrate supplementation on intake, digestibility, and grazing time of lactating beef cows.

Abstract: To establish the effect of sward height (SH) and concentrate supplementation on performance of grazing cattle, 24 crossbred Angus beef cows (535 kg BW) and calves (114 kg BW) were grouped by weight and calving date. They were randomly assigned to two SH treatments, either 4 to 8 cm or 8 to 11 cm, and fed three levels of supplement, high, low, or none, consisting of 6.24, 3.12, and 0 kg x animal(-1) x d(-1), respectively. The experiment was repeated over three 15-d periods in 1996: May (P1), June/July (P2), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…Esse resultado indica que a estrutura do dossel ou o resíduo nos últimos dias de pastejo dificultou a colheita de forragem pelos animais, o que está de acordo com a afirmativa de Hodgson (1990), que relatou efeito da estrutura e da composição botânica da pastagem sobre a ingestão de forragem por animais em pastejo. Contudo, Gekara et al (2001) observaram aumento no tempo de pastejo em resposta à redução na altura do dossel e, conseqüentemente, à menor quantidade de massa seca de forragem no pré-pastejo.…”
Section: Resultsunclassified
“…Esse resultado indica que a estrutura do dossel ou o resíduo nos últimos dias de pastejo dificultou a colheita de forragem pelos animais, o que está de acordo com a afirmativa de Hodgson (1990), que relatou efeito da estrutura e da composição botânica da pastagem sobre a ingestão de forragem por animais em pastejo. Contudo, Gekara et al (2001) observaram aumento no tempo de pastejo em resposta à redução na altura do dossel e, conseqüentemente, à menor quantidade de massa seca de forragem no pré-pastejo.…”
Section: Resultsunclassified
“…This increase in total DMI has been observed for cattle that are either grazing or fed high forage diets and supplemented with concentrate or fiber-based supplements Bodine et al, 2001;Sanson and Clanton 1989;Matejovsky and Sanson, 1995;Gekara et al, 2001;Goetsch et al, 1991). Most feeds have substitution rates that are less than one and greater than zero Bodine et al, 2001;Sanson and Clanton 1989;Matejovsky and Sanson, 1995;Gekara et al, 2001;and Goetsch et al, 1991) which results in a net increase in total DMI and increased animal productivity. observed that dairy cows grazing at high and low pasture allowances had increased total DMI as concentrate was supplemented at 8.63 kg/d.…”
Section: Effects Supplementation On Total Dry Matter Intakementioning
confidence: 86%
“…Bodine et al (2001) found that steers supplemented with protein increased total OM intake and improved BW gain. In spite of substitution, total DMI is quite often increased, even with cattle at different stages of production and consuming forages of different quality as indicated by reported substitution rates less than one Bodine et al 2001;Sanson and Clanton 1989;Gekara et al 2001;and Goetsch et al 1991). Only in certain situations, such as supplementation of low quality forage with high protein supplement, can an increase in forage intake be observed as well.…”
Section: Effects Supplementation On Total Dry Matter Intakementioning
confidence: 99%
See 2 more Smart Citations